Developing an undergraduate degree in entrepreneurship: The case of Universiti Utara Malaysia - Hashim, Norashidah; Bakar, Habshah; Mohamad, Armanurah; Din, Mohd Salleh (2004)
The proponent of "entrepreneurs are made and not born" emphasizes on programmes of developing entrepreneurs through education and training. Universiti Utara Malaysia, being a management university in Malaysia took the lead in offering the Bachelor in Entrepreneurship (Hons) degree. This paper will discuss on the historical development of designing the programme, focusing on the philosophy of the programme, the development of the courses, and its implementation.